Peran Motivasi Spiritual Agamis terhadap Organizational Citizenship Behavior (OCB) dan Kinerja Dosen (Studi pada Dosen Universitas Haluoleo Kendari) - Adam, La Ode Bahana (Universitas Brawijaya, Indonesia, 2012)
This study is designed to test and prove empirically the role of religious spiritual motivation, both directly and indirectly, through organizational citizenship behavior (OCB) on lecturers'performance.Specifically, the purpose of this study is to analyze and empirically explore the role of : (1) aqeedah motivation on organizational citizenship behaviour (OCB), (2) ebada motivation on organizational citizenship behavior (OCB), (3) mu'amalah motivation on organizational citizenship behavior, (4) aqeedahmotivation on lecturers'performance, (5) ebada motivation on lecturers'performance, (6) mu'amalah motivation on lecturers'performance, and (7) organizational citizenship behavior (OCB) on lecturers'performance. The study is expected to enrich and expand the literature in management science, particularly in the area of human resource development motivation of employees and organizational behavior which will be useful for academics and practitioners. The population of this study are all lecturers in HaluoleoUniversity of Kendari which spreads out at 8 faculties. The samples are 120 lectuers, chosen using proportional sampling technique, and the analysis of the data uses PLS (Partial Least Square). The main conclusion of this study is that the performance of lecturer may be better if the ebada spiritual motivation is increased, especially in the understanding of religious values to the concepts of work, behaviour and performance in a religious point of view.